Evaluation of Albumin Administration Pattern in a Teaching University Affliated Hospital in Iran - Leila Zarepour; Mohammad Mehdi Saghafi (Research Center for Rational Use of Drugs (RCRUD), 2020)
Background: Albumin has long been a critical medication in many hospitalized cases, especially for patients in the intensive care unit (ICU) section. Some adverse clinical impacts and economic limitations have made the human albumin an appropriate therapeutic agent for extensive analyses. Materials and Methods: This retrospective follow-up study was performed in Firozabadi hospital as a General Medical Teaching and Research Center with 12 major units and ICU sections. Information of the patients was collected based on the charts, physician and the nursing reports. We evaluated all 153 patients who used albumin in Jan to June 2016 (first 6-months) before guideline distribution and then during Jan to June 2018 (second 6-months).  Results: We evaluated current management protocols for hypoalbuminemia, sepsis shock, nephrotic syndrome, hepatorenal syndrome, CVA (Cerebrovascular Accident), cirrhosis, electrolyte disorder, cardiovascular surgery, edema and ARDS (Acute Respiratory Distress Syndrome). During this study, we found that before guideline distribution, 297 numbers (27.1% of total prescribed albumin vials) of albumin vials prescribed for 20 patients (18.6%); while after 18-month interval, guideline adoption the second 6-month administration pattern was less inappropriate; Nevertheless, the number of patients, vials, duration and level of albumin was different in comparison with the first evaluated group and were more accordant with standard instructions.  Conclusion: A considerable change in administration strategies would be observed after executing the standard operating procedures and confirms that this approach might remarkably alter the physician's attitude toward more rationalized prescription of critical agents that subsequently reduce the associated implied costs on health systems.